Efficient enzymatic hydrolysis of chitin into N-acetyl glucosamine using alkali as a recyclable pretreatment reagent. Issue 8 (15th April 2021) - Zhang, Alei; Wang, Chengyong; Chen, Jie; Wei, Guoguang; Zhou, Ning; Li, Ganlu; Chen, Kequan; Ouyang, Pingkai
Abstract : In this study, an alkali freeze–thaw pretreatment protocol was investigated to efficiently enhance enzymatic hydrolysis of chitin into GlcNAc at high concentrations. Abstract : In this study, an alkali freeze–thaw pretreatment protocol was investigated to efficiently enhance enzymatic hydrolysis of chitin into N -acetyl glucosamine (GlcNAc) at high concentrations. The optimal conditions for alkali freeze–thaw treatment of chitin were determined to be an alkali concentration of 8% (w/v), a temperature of −25 °C, twice freeze–thaw cycles in 12 h, and a substrate concentration of 4% (w/v). This treatment caused chitin powder to acquire a visible fibrillar structure, with scanning electron microscopy and Brunauer–Emmett–Teller analysis showing that the surface of chitin changes from a dense structure to a nanofibrillar structure (diameter 30–50 nm) with increased surface areas after the treatment. Moreover, Fourier-transform infrared spectroscopy, thermogravimetric analysis, elemental analysis, X-ray diffraction, and intrinsic viscosity analysis revealed that the crystallinity, molecular weight, and thermal stability of the chitin decreased upon pretreatment without alteration of the chemical structure or deacetylation. Interestingly, facile recovery of the alkali solution can be realized after the precipitation of chitin via boiling and centrifugation, and the recovered alkali aqueous solution can be reused without decreasing the subsequent treatment effect. Additionally, the GlcNAc concentrations from the fed-batch enzymatic hydrolysis of chitin treated with KOH and NaOH can reach up to 75 g L −1 and 68 g L −1 over 18 h, respectively. Thus, this work demonstrates a clean, sustainable, and efficient procedure to convert chitin into GlcNAc.